2023
DOI: 10.1021/acs.jpcb.3c00747
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of the Low-Temperature Crossover of Water in Hard Confinement

Abstract: The dynamics of water confined in mesoporous MIP (2–3 nm pores in size) with silica gel (secondary silica; further, the abbreviation SG will be used) and MAP (10–35 nm pores in size) without SG borosilicate glasses have been studied by broadband dielectric spectroscopy (BDS), nuclear magnetic resonance (NMR), and differential scanning calorimetry (DSC). MIP samples contain secondary silica inside the pores and provide a confinement size of about 2–3 nm, whereas MAP samples are free of secondary silica and prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 81 publications
(167 reference statements)
0
2
0
Order By: Relevance
“…Therefore, the properties of this so-called interfacial or hydration water may reveal specific features of water–polymer interactions. 15,21–25 Among other issues, the non-freezing fraction of adsorbed water, 18,26,27 the confinement of water molecules 28,29 and the process of ice formation at sub-zero temperatures and the dynamics in partially crystallized water mixtures 30–37 are topics that provide insight into the properties of hydration water. Especially for polysaccharides, it is known that a small amount of water significantly affects the T g of the hydrated polysaccharide by disrupting inter-molecular hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the properties of this so-called interfacial or hydration water may reveal specific features of water–polymer interactions. 15,21–25 Among other issues, the non-freezing fraction of adsorbed water, 18,26,27 the confinement of water molecules 28,29 and the process of ice formation at sub-zero temperatures and the dynamics in partially crystallized water mixtures 30–37 are topics that provide insight into the properties of hydration water. Especially for polysaccharides, it is known that a small amount of water significantly affects the T g of the hydrated polysaccharide by disrupting inter-molecular hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have revealed that materials adjacent to a solid and near-surface can exhibit interfacial regions of reduced density, interfacial freezing, interfacial melting, molecular layering, molecular orientation, or specific lateral molecular arrangements . Consequently, significant deviations in their properties, such as flow and intermolecular entanglements, local chain mobility, glass transition temperature, diffusion, tautomerization, or crystallization, are noted when compared to bulk samples. Due to these facts, confined systems hold promise for diverse industrial applications, including nanolithography, lubrication, paints, surface treatments, and elastic membranes.…”
Section: Introductionmentioning
confidence: 99%